Peak performance age in sport: the typical Olympian is getting older - Quillen, D.; Dean, S. (ARC Centre of Excellence in Population Ageing Research, 2021)
A fact sheet on peak performance age in sport, released by the ARC Centre of Excellence in Population Ageing Research (CEPAR), analyses the age at which athletes are competing at their best and how the typical age has changed over time. The study provides insights about how human abilities change with advancing years and how this plays out in the careers of elite athletes as well as for recreational athletes in community sport.